A Critical Assessment of Adolescence, the Characteristics and Developmental Tasks of Adolescent in the Contemporary World - Udom, Bassey S.; Udongwo, Grace Effiong (European Journal of Life Safety and Stability (2660-9630), 2022)
This paper carefully discussed adolescence and adolescence psychology in the contemporary world. Adolescents are a distinct group, no longer children but not yet adults, and, as such, have unique needs. It was discovered in this paper that the rate at which adolescents experience changes varies depending on gender, genetics, environmental factors, and health. Adolescence can be broken into three stages: early adolescence, middle adolescence, and late adolescence. Each stage has its own characteristics. Early adolescence is the first stage and occurs from age 10 to 14. This stage usually begins with puberty. The middle adolescence is the second stage and occurs from age 15 to 17. Teenagers at this stage are extremely concerned with how they look. Late adolescents generally have completed physical development and have grown to their full adult height. This paper concluded that biological changes that take place during puberty have a tremendous effect on an adolescent psychologically. One of the changes, for example, is menarche. One of the recommendations made was that since strong and loving relationships can have a direct and positive influence on adolescents, it is therefore advisable that adolescents avoid alcohol intake and other drugs, get enough regular sleep, develop and maintain good eating habits, and stay physically active. This can directly promote their psychological and emotional wellbeing.